China's International Behavior Activism, Opportunism, and Diversification - Medeiros, Evan S. (RAND Corporation, 2009)
China is now a global actor of significant and growing importance. It is involved in regions and on issues that were once only peripheral to its interests, and it is effectively using tools previously unavailable. China's international behavior is clearly altering the dynamics of the current international system, but it is not transforming its structure.China's global activism is continually changing and has so many dimensions that it immediately raises questions about China's current and future intentions. This study provides a conceptual and empirical framework to assess these important trends. It examines how China views its security environment, how it defines its international objectives, how it is pursuing them, and the consequences for U.S. economic and security interests.